Persepsi Masyarakat Tentang Judul Berita Clickbait Pada Media Kumparan.Com Pada Masyarakat Kelurahan Desa Lama Kecamatan Pancur Batu - Hadynda Wahyusuci; Abdul Haris; Bahrum Jamil (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2022)
The title of this research is Public Perception in Addresing Clickbait News  on Kumparan.com Media (Descriptive Study on the Kelurahan Desa Lama, Kecamatan Pancur Batu). This research was backround because of the proliferation of clickbait news hat spread to the public through Kumparan social media. The aim of the study was to learn how to public perception of clickbait headlines on Kumparan.com media. This study aims to uses  and gratification theory. In collecting data, the researchers conducted face-to-face interviews with five informants who were active community users of Kumparan media in the Desa Lama, Pancur Batu District. This research uses qualitative research. The results of the current study are that many forms of clickbait titles content in Kumparan are often seen by informants. The news title ‘’ 31 Years as a Contract Worker for the NTT Provincial Government in Sikka, Layoff Only by Phone’’ which is a type of clickbait Exaggeration also influenced the informant’s perception of clickbait news titles that were spread through social media. For this reason, reading the truth of the information seen on social media is an important thing that must be done to further ensure that information the clickbait headline is true or tricky.